Lectotypification of Spiraea yunnanensis Franchet var. siccanea W. W. Smith (Rosaceae) - Xu, Dong-Xian; Liu, Quan-Ru (Phytotaxa, 2016)
Spiraea yunnanensis Franchet (1890: 200) var. siccanea W. W. Smith (1917: 69) was described on the basis of two collections, G. Forrest 9912 and 9972, from Yunnan province, China, but without indicating the type. These specimens should be treated as syntypes in accordance with Article 9.5 of the ICN (McNeill et al. 2012). Rehder (1933: 205) treated it as a distinct species and considered it could be easily distinguished from S. yunnanensis by the leaf blades being adaxially glabrous (vs. pilose) and abaxially sparsely pilose (vs. densely white tomentose). Although this treatment is accepted by latter botanists, its type is still not designated (Yu & Lu 1974, Wu 1984, Lu & Crinan 2003, Zhou & Xu 2006, Businský 2011). We traced nine specimens that fit the protologue, i.e. five duplicate specimens labeled “G. Forrest 9972” (barcodes A00033520, BM000622233, E000385320, K000737489, PE00703468) and four duplicate specimens labeled “G. Forrest 9912” (A00033519, BM000622232, E00385319, K000737490). The specimen (G. Forrest 9972, barcode E000385320) is better preserved and more complete, and W. W. Smith worked at E as deputy keeper in 1911–1922 (Stafleu & Cowan 1985), therefore we designate it as the lectotype for this taxon.